Co-secretion of calcitonin gene-related peptide, gastrin-releasing peptide and ACTH by a carcinoid tumour metastasizing to the cerebellum. Issue 736 (February 1987) - Ghatei, M. A.; Stratton, M. R.; Allen, J. M.; Joplin, G. F.; Polak, J. M.; Bloom, S. R.
Abstract : A carcinoid tumour presenting as Cushing's syndrome is reported. Although no tumour mass could be initially identified the patient returned with first a liver and subsequently a cerebellar mass both of which were resected. Only at post-mortem was the lung primary discovered. ACTH, gastrin-releasing peptide (GRP) and calcitonin gene-related peptide were elevated in plasma before resection of the hepatic tumour. These peptides were demonstrated in both the hepatic and cerebellar tumours by immunocytochemistry and radioimmunoassay. This case illustrates the occasional tendency of primary lung carcinoids to remain small and clinically undetectable while generating secondary tumours which are symptomatic. It is suggested that immunological demonstration of GRP may be diagnostically helpful in directing attention to the lung as a primary site in neuroendocrine tumours which present in this fashion.